A sustainable lithium bromide-water absorption cooling system using automobile engine waste heat: Theoretical study. - Mohammed Qasim Shaheen; Salman Hashim Hammadi (PLoS ONE)
This manuscript investigates the utilization of waste heat from automobiles, such as exhaust gas and engine coolant water, to run a lithium bromide water Absorption Cooling System (ACS). This study proposed adding a secondary heat exchanger located between the primary heat exchanger and generator. It takes heat from engine coolant water to reduce thermal load on the generator and to enhance the Coefficient of Performance (COP) of the system. The effect of concentration solution, primary heat exchanger effectiveness, and the temperature of main component (generator, condenser, evaporator and absorber) are studied. The results show a COP of 0.79 with a cooling capacity of 5 kW at generator, condenser, evaporator, and absorber temperatures of (90, 40, 10, and 35), respectively. The COP increases as the evaporator temperature increases, and it decreases as the condenser and absorber temperature increases. Also, any increase in the heat exchanger effectiveness will be led to increase the COP. The results show that the addition of a secondary heat exchanger led to reduce the load on the generator by 4% to 7%, and that depends on the operating conditions and the system. In addition, the results examine a significant reduction in CO2 emissions by 1.58 kg/hr. These findings point out to a substantial possibility for lowering thermal emissions and increasing energy efficiency, and that provides a long-term way to use waste energy in automobiles.